L-Ascorbic acid preferentially kills KRAS mutant pancreatic cancer cells through DNA damage - Hye-Lim Jang; Seung Tae Kim; Jung Yong Hong; Kee-Taek Jang; Jinseok Heo; Hong Jae Chon; Young Suk Park; Joon Oh Park (Scientific Reports)
Abstract Pancreatic cancer (PC) is a worldwide leading cause of cancer-related death. Despite recent progress using immunotherapy with checkpoint inhibitors or targeted agents in various solid tumors, these approaches have not been successful in PC. Therefore, there is an urgent unmet need for the development of novel therapeutics for these difficult-to-treat patients. We hypothesized that high-dose L-ascorbic acid (AA) could disrupt redox homeostasis and selectively inhibit the viability of PC cells harboring KRAS mutations; thus, we investigated the molecular mechanism of AA cytotoxicity in PC cell lines (Hs 700T, BxPC-3, HPAC, HPAF-II, PANC-1, SU.86.86, and Hs 766T) and patient-derived cells (PDCs; PR11-043T and PR11-077T)), identifying a subset of patients who may benefit from AA therapy and opening an avenue for further clinical development. In this preclinical study, we found that AA efficiently inhibited the growth of KRAS G12D-mutant PC cells. Mechanistically, this was due to selective glycolysis inhibition via GAPDH inactivation and DNA damage, in PC cell lines harboring KRAS G12D. We also showed that AA synergizes with the DNA-damaging agent AZD6738 in PC cells and AA induces an enhanced DNA damage response in BRCA mutant PC cells, as confirmed in PC PDCs having with KRAS G12D or BRCA1/2 mutation. This study showed the antitumor activity of AA in PC cells and PDCs, indicating that KRAS G12D identifies an attractive subset of PC cells for treatment using AA and novel agents targeting key molecules involved the DNA damaging pathway. In addition, DNA damage response (DDR)-defective cell subsets, including germline BRCA1/2 mutants, may be potential candidates for this novel approach, which provides new insights for future clinical development.